PERBANDINGAN KINERJA PENGECORAN ANTARA CONCRETE-BUCKET DAN CONCRETE-PUMP PADA PROYEK BANGUNAN BERTINGKAT - Rachmi Yanita; Nurdiyanto Nurdiyanto (Racic : Rab Construction Research, 2023)
In the implementation of cast in situ concrete construction, the casting method is well planned so that it can be completed on time with an efficient cost. The casting method that is commonly used is to use a concrete-pump and concrete-bucket which are used together, especially for high-rise buildings. This study aims to obtain the time, cost and productivity of concrete casting work on floor plates, beams and columns of a study project in Jakarta, especially on floors 7 to 11 which are typical floors, using the column concrete-bucket method and concrete-pump for slabs and beams. . An analysis was carried out on the stages of the work procedure, the time and cost of casting and the productivity of the two casting methods according to the volume of the beam and column plates.The results of the analysis show that the time and productivity for each floor are different because the higher the floor elevation, the longer the processing time will be, so the productivity will decrease. It is obtained that the cost for operating a casting tool using a Concrete Pump is Rp. 76,727,868 or IDR 81,270.912/m3, with a faster processing time of 7.58 minutes/m3 and higher volume per hour productivity than the concrete bucket. Meanwhile, the cost of a concrete-bucket used simultaneously for casting a column is higher than that of a concrete pump, reaching Rp. 53,388,724 or IDR 127,877.183/m3 because it is related to the use of a Tower Crane. Keywords: Casting method, concrete pump, concrete bucket, productivity, time and cost